Innovation and Challenges of Musyarakah Contracts in Islamic Financial Institutions: Fintech Integration, Smart Contracts, and the Role in MSME Financing (Empirical and Policy Review, 2021–2025) - Lisvi Vahlevi, Dewi Riza (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2025)
Background. The acceleration of financial digitalization in the 2021–2025 period has encouraged Lembaga Keuangan Syari’ah (LKS) to develop musyarakah contract innovations through fintech integration and the use of blockchain-based smart contracts, as well as making musyarakah a strategic instrument in strengthening the productive financing of MSMEs. Aim. This research aims to analyze the development of these innovations as well as identify regulatory, operational, and technological challenges that affect the effectiveness of their implementation in the Islamic finance industry. Methods. Using empirical and policy review methods with a mixed-method approach including secondary data analysis from the Otoritas Jasa Keuangan, Islamic banking and fintech reports, academic studies 2021–2025, as well as thematic qualitative analysis of regulations and fatwas. Results. This study found that the integration of fintech and smart contracts can improve transparency, monitoring accuracy, speed of the financing process, and mitigation of moral hazard risks in musyarakah schemes, while the main challenges are related to regulatory fragmentation, readiness of digital infrastructure of LKS, data security risks, and low sharia technology literacy. These findings emphasize the need for policy harmonization, standardization of sharia smart contracts, and collaboration between regulators, LKS, and fintech players to maximize the potential of deliberation in supporting the empowerment of MSMEs in the digital economy era.